A comprehensive study of the tides around the Welsh coastal waters. (5th June 2021) - Horrillo-Caraballo, J.M.; Yin, Y.; Fairley, I.; Karunarathna, H.; Masters, I.; Reeve, D.E.
Abstract: A computational model has been used to explore characteristics of the barotropic tide around the Welsh coast in detail for the first time. Proper understanding of tidal characteristics is vital for the sustainable use of marine resources; particularly for industries such as marine energy extraction, aggregate mining, aquaculture, as well as regulators and agencies with responsibilities for the resource management and public safety. In shallow water areas, the influence of bathymetry and energy dissipation leads to the generation of higher harmonics that cause complex tidal phenomena. The Celtic and Irish seas, which enclose the Welsh coast (UK), are heavily industrialised shallow water seas with macro-to mega-tidal semi-diurnal tides. It is shown that tidal distortion is significant in the Bristol Channel (S. Wales) and in the large shallow estuaries of the N. Wales coast; for much of the west coast this is only significant in localised areas around headlands and islands. Tidal dominance switches from flood dominant in the south and north to ebb dominant on the west coast. Highly complex patterns of vorticity in the tidal residual flow are noted. All these factors mean that careful siting of industry and coastal management interventions is required to avoid disruption of the natural system. Highlights: We present a high resolution model of barotropic tidal dynamics around Wales. Model validation is performed against extensive coastal observations. The M2 tide is dominant with M4, MS4, MN4, M6, 2MS6 contributing to tidal asymmetry. Tidal ellipses indicate predominantly bi-directional tidal currents. Numerous gyres are evident in the residual flow pattern.